Anti‐Alzheimer's multitarget‐directed ligands with serotonin 5‐HT6 antagonist, butyrylcholinesterase inhibitory, and antioxidant activity. Issue 7 (4th June 2019) - Marcinkowska, Monika; Bucki, Adam; Panek, Dawid; Siwek, Agata; Fajkis, Nikola; Bednarski, Marek; Zygmunt, Małgorzata; Godyń, Justyna; Del Rio Valdivieso, Alvaro; Kotańska, Magdalena; Kołaczkowski, Marcin; Więckowska, Anna
Abstract: Serotonin 5‐HT6 receptors, butyrylcholinesterase (BuChE) and oxidative stress are related to the pathophysiology of Alzheimer's disease. Inhibition of BuChE provides symptomatic treatment of the disease and the same effect was demonstrated for 5‐HT 6 antagonists in clinical trials. Oxidative stress is regarded as a major and primary factor contributing to the development of Alzheimer's disease; therefore, antioxidant agents may provide a disease‐modifying effect. Combining BuChE inhibition, 5‐HT 6 antagonism, and antioxidant properties may result in multitarget‐directed ligands providing cognition‐enhancing properties with neuroprotective activity. On the basis of the screening of the library of 5‐HT 6 antagonists against BuChE, we selected two compounds and designed their structural modifications that could lead to improved BuChE inhibitory activity. We synthesized two series of compounds and tested their affinity and functional activity at 5‐HT 6 receptors, BuChE inhibitory activity and antioxidant properties. Compound 12 with K i and K b values against 5‐HT 6 receptors of 41.8 and 74 nM, respectively, an IC 50 value of 5 µM against BuChE and antioxidant properties exceeding the activity of ascorbic acid is a promising lead structure for further development of anti‐Alzheimer's agents. Abstract : New indole‐based multitarget‐directed ligands merging inhibitory activity against BuChE, antagonistic activity at 5‐HT6 receptors and antioxidant properties were designed, synthesized, and evaluated in vitro. Due to its multidirectional in vitro activity, compound 12 (2‐(3‐(4‐(1‐(3‐chlorobenzyl)‐1 H ‐indol‐4‐yl)piperazin‐1‐yl)propyl)isoindoline‐1, 3‐dione) appears as a good starting point for further development of anti‐Alzheimer's agents.